Analisa Strukturalisme Genetik pada Komik Buddhis Aṅgulimāla - Dahlia Dahlia (Jurnal Budi Pekerti Agama Buddha, 2025)
Handaka Vijjananda's Buddhist comic "Aṅgulimāla: True Repentance" depicts the repentance of a ruthless murderer who undergoes spiritual transformation after meeting Gautama Buddha. This story not only conveys Buddhist moral teachings but also reflects the social, cultural, and religious dynamics of ancient Indian society. This study aims to analyze the intrinsic and genetic structures of the Buddhist comic "Aṅgulimāla" using Lucien Goldmann's genetic structuralism approach. The method used is qualitative descriptive, with the primary data source being the comic "Aṅgulimāla." Data collection techniques were conducted through intensive reading and note-taking, while data analysis was conducted by linking the intrinsic elements of the literary work with the socio-historical context and the author's worldview. The results show that the intrinsic structure of the comic "Aṅgulimāla" includes themes of repentance, karma, loving-kindness (metta), and wisdom; strong characters and characterizations; a progressive plot; internal and external conflicts; and a time, place, and social setting that reflect 6th-century BCE Indian society. Meanwhile, its genetic structure reveals human facts such as the caste system, power relations, and social morality, as well as the author's worldview, which emphasizes Buddhist values such as compassion, self-transformation, and hope for human moral change. Thus, genetic structuralism analysis confirms that the comic Aṅgulimāla is a literary work that is not only narrative in nature but also reflects social realities and humanitarian messages relevant to modern life.